Designing the Concept of Regional Innovation Sustainability: The Triple Bottom Line Concept Approach and Sustainable Evaluation - Ammar, Muhammad; Bangsawan, Gema; Asriani, Asriani (Jurnal bina praja, 2024)
Sustainability of performance target achievement. While quantitative target achievement has reached an ideal state, it is often accompanied by a lack of sustainability as a continuous cycle. This cycle should be established from the inception of regional innovations, preventing them from becoming a burden on the government due to the utilization of various resources, including budget, time, and innovation actors. This research employs a qualitative approach with literature review data analysis to explore research perspectives and establish a framework aligned with the research subject. This approach facilitates developing or deepening theories and insights into the research subject. Previous research has focused on applying sustainability concepts within companies or corporations to enhance economic growth (revenue), social responsibility (community), and environmental sustainability. This research formulates a conceptual design for a sustainability assessment standard using empirically tested indicators for local governments. The concept utilizes the triple bottom line (TBL) approach, encompassing three dimensions: prosperity, people, and planet. These three dimensions serve as the focal points of intervention within the sustainability framework of this concept. The concept evaluates the potential for developing and continuing existing practices or, alternatively, identifies opportunities for cessation and replacement with more effective and efficient implementation methods through economic, social, and environmental dimensions. This research successfully develops an evaluation matrix for assessing regional innovation and establishes indicators that can be used as measurement tools within local government organizational units at smaller scales. However, the research is limited in its ability to generalize sustainability from a single framework or concept to diverse concepts tailored to the specific conditions of individual local governments. Time and methodological constraints also limit the scope of the research, leaving room for further refinement and expansion in future studies.